Serotype analysis of rotaviruses from different locations in Malaysia. - Rasool, N.B.; Green, K.Y.; Kapikian, A.Z. (American Society for Microbiology, 1993)
The distribution of rotavirus G (VP7) serotypes circulating in four locations in Malaysia, representing three geographical areas, was evaluated in 341 RNA-positive stool specimens obtained discontinuously between 1977 and 1988 from infants and young children under the age of five years who were hospitalized with acute gastroenteritis. A total of 306 specimens (256 stool suspensions and 50 that were adapted to growth in tissue culture) that were rotavirus positive by the confirmatory enzyme-linked immunosorbent assay (ELISA) were examined for serotype by ELISA utilizing monoclonal antibodies to rotavirus G serotype 1, 2, 3, 4, or 9. One hundred eighty (59%) of the 306 specimens could be serotyped; of these 180 specimens, 71% were serotype 4, 15% were serotype 1, 4% were serotype 2, and 4% were serotype 3. Serotype 9 rotavirus was not detected. Most (71%) of the specimens tested were obtained in 1988, when serotype 4 predominated in three locations in West Malaysia; no single serotype was predominant in a limited number of specimens from East Malaysia.